TRUE SHALLOT (Allium cepa var ascalonicum) SEED PRODUCTION DURING OFF SEASON - Ramadhani Eka Putra; D Beta Ramadan; Adriyanita Adin; Ida Kinasih; Mia Rosmiati; Indah Oktaviani; Sovia Santi Leksikowati (SEAMEO BIOTROP, 2021)
The application of seed for true shallot cultivation is an alternative of the more common cultivation practice, in which 30% of harvested tubers used for cultivation purposes. The seed production of this temperate tuber, in the tropical region, is quite challenging due to low flowers and seed formation. Several studies showed that vernalization (cold induction) and application of Benzil Amino Purin (BAP) could be applied to improve flowering and seed production. However, such studies were conducted during the best cultivation period for about 3 months and thus, limit the production period of seeds. This study was conducted to observe the effect of both methods outside cultivation periods to flower and capsule numbers, fruit set, and weight of 100 seeds compared with common cultivation. In this study, bulbs of onion vernalized at 10oC for 30 days then became subjected to synthetic hormone (BAP) prior planted while control group The results showed that BAP treated shallot group has the lowest values for all observed parameters (1552.67, 312.11, 22.5%, 0.2244 gram) compared to those vernalization treated group (1592.44, 623, 30.5%; 0.2261 gram) and control group (6774.67; 3898.44; 57.06%; 0.3304 gram). Based on this study, it could be concluded that common cultivation is a better method to produce true shallot seeds during the offseason.